Creating microclimate in-trailers cars for chicks - Vasylenkov, V.; Pogrebnyj, D. (Energy and Automation, 2015)
In the article the thermal calculation poultry house on wheels to determine the amount of ventilation calculate the amount of air supplied per hour for 1 kg of live weight of the chicks, the multiplicity of air and according to this selection of ventilation equipment required performance.